Exploring the Exclusive Isolation of Pseudomonas syringae in Peltigera Lichens via metabolite analysis and growth assays ... : Exploring Isolation of P. syringae in Peltigera ... - Ramirez, Natalia (Zenodo, 2024)
Lichen samples from Iceland were collected from the genera Peltigera, Cladonia, and Stereocaulon in March 2023 at Heidmork forest, Oskjuhlid hill, and the shores of Ellidaa in Arbaejarstifla. All specimens underwent morphological analysis, and corresponding vouchers have been deposited at the Icelandic Institute of Natural History. ...